2014
DOI: 10.1016/j.ijdevneu.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Embryological exposure to valproic acid disrupts morphology of the deep cerebellar nuclei in a sexually dimorphic way

Abstract: Autism spectrum disorders (ASD) is diagnosed in males at a much higher rate than females. For this reason, the majority of autism research has used male subjects exclusively. However; more recent studies using genetic sex as a factor find that the development of the male and female brain is differentially affected by ASD. That is, the natural sex-specific differences that exist between male and female brains lead to sexually dimorphic expressions of autism. Here we investigate the putative sexual dimorphism th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 92 publications
0
16
0
Order By: Relevance
“…VPA exposure leads to decreased thickness of the PFC and the basolateral amygdala at early ages, and of the hippocampal CA1 at all ages [332]. Other brain areas that are affected include the cerebellum which decreases in size [247], and the amygdala which increases in size [265]. …”
Section: Lessons From Animal Modelsmentioning
confidence: 99%
“…VPA exposure leads to decreased thickness of the PFC and the basolateral amygdala at early ages, and of the hippocampal CA1 at all ages [332]. Other brain areas that are affected include the cerebellum which decreases in size [247], and the amygdala which increases in size [265]. …”
Section: Lessons From Animal Modelsmentioning
confidence: 99%
“…Purkinje cell abnormalities were male-specific in the Reeler mouse model of ASD, and the Adnp mouse model of ASD shows sex-specific hippocampal gene expression, behavior alterations, and response to treatment [224,225]. The VPA mouse model shows complex patterns of sex specificity in androgen receptor expression and deep cerebellar nuclei morphology [226,227]. …”
Section: Multi-hit Hypothesis: (Epi)gene X Environment X Sex Interactmentioning
confidence: 99%
“…[ 92 ] subsequently reported the selective overexpression of two subunits of the NMDA receptor and the commonly linked kinase calcium/calmodulin-dependent protein kinase II, indicating that VPA strongly stimulates NMDA receptor-mediated transmission and promotes plasticity in the neocortex. Mowery et al [ 93 ] also found higher cell counts in male than in female VPA rats, indicating a stronger but more aberrant local plastic reaction to VPA in males.…”
Section: Reviewmentioning
confidence: 99%